Consistency and stability analysis of models of a monetary growth imperative - Oliver Richters; Andreas Siemoneit (Vereinigung für Ökologische Ökonomie (VÖÖ), 2016)
Is fostering economic growth a question of political will or "unavoidable" to maintain economic stability? It is disputed whether such 'growth imperatives' are located within the current monetary system, creating a conflict with sustainability. To examine the claim that compound interest causes the growth imperative, we present five post-Keynesian models and perform a stability analysis in the parameter space. A stationary state with zero net saving and investment can be reached with positive interest rates, if the parameter "consumption out of wealth" is above a threshold that rises with the interest rate. The other claim that retained profits from the interest revenues of banks create an imperative is based on circuitist models that we consider refutable. Their accounting is not consistent, and a modeling assumption central for a growth imperative is not underpinned theoretically: Bank's equity capital has to increase even if debt does not. This is a discrepancy between the authors' intentions in their texts and their actual models. We conclude that a monetary system based on interest-bearing debt-money with private banks does not lead to an "inherent" growth imperative. If the stationary state is unstable, it is caused by decisions of agents, not by structural inevitableness. – – Ist das Streben nach Wirtschaftswachstum eine Frage des politischen Willens oder eine notwendige Bedingung für ökonomische Stabilität? Es ist umstritten, ob solche "Wachstumszwänge" im heutigen Geldsystem bestehen, und einen Konflikt mit Nachhaltigkeit hervorrufen. Zur Untersuchung der ersten Behauptung, dass Zinseszinsen einen Wachstumszwang hervorrufen, stellen wir fünf post-Keynesianische Modelle vor und führen eine Stabilitätsanalyse im Parameterraum durch. Eine stationäre Ökonomie mit Spar- und Investitionsquote von null kann bei positivem Zinssatz erreicht werden, wenn der Parameter "Konsum aus dem Bestand" oberhalb eines Schwellenwerts liegt, der mit dem Zinssatz ansteigt. Die andere Behauptung, dass die Bildung von Gewinnrücklagen aus den Zinseinnahmen der Banken zu einem Wachstumszwang führt, basiert auf Modellen des monetären Kreislaufs die wir für widerlegbar halten. Ihre Bilanzierung ist inkonsistent, und eine zentrale Modellannahme ist nicht theoretisch begründet, aber die Hauptursache des Wachstumszwangs: Das Eigenkapital der Bank muss gesteigert werden, selbst wenn ihre Verbindlichkeiten nicht wachsen, was eine Diskrepanz zwischen der Intention der Autoren und dem eigentlichen Modell ist. Wir kommen zum Schluss dass das heutige Geldsystem auf der Basis von zinstragendem Kreditgeld mit privaten Banken nicht zu einem "inhärenten" Wachstumszwang führt. Falls der stationäre Zustand instabil ist, liegt es an Entscheidungen wirtschaftlicher Agenten und nicht an struktureller Unvermeidbarkeit.
Keywords: 330; Ecological Macroeconomics; Zero Growth; Growth Imperative; Monetary Economy; Ökologische Makroökonomik; Nullwachstum; Wachstumszwang; monetäre Ökonomie